(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Vitiligo is a chronic autoimmune depigmentation disorder affecting 0.5-2% of the global population. Destruction of epidermal melanocytes is driven primarily by CD8 cytotoxic T lymphocytes through IFN-γ-CXCL9/CXCL10-CXCR3 signaling axis and JAK/STAT pathway activation. When conservative therapies fail, invasive surgical correction - including punch grafting, suction blister grafting, split-thickness skin grafting, and non-cultured melanocyte-keratinocyte transplantation - offers clinically meaningful repigmentation. This review synthesizes current immunopathogenetic data with quantitative outcomes of major invasive techniques.